NHC‐Containing Manganese(I) Electrocatalysts for the Two‐Electron Reduction of CO21. (2nd April 2014) - Agarwal, Jay; Shaw, Travis W.; Stanton, Charles J.; Majetich, George F.; Bocarsly, Andrew B.; Schaefer, Henry F.
Abstract The synthesis and characterization of the first catalytic manganese N‐heterocyclic carbene complexes are reported: MnBr(N‐methyl‐N′‐2‐pyridylbenzimidazol‐2‐ylidine)(CO)3 and MnBr(N‐methyl‐N′‐2‐pyridylimidazol‐2‐ylidine)(CO)3. Both new species mediate the reduction of CO2 to CO following two‐electron reduction of the MnI center, as observed with preparative scale electrolysis and verified with 13CO2. The two‐electron reduction of these species occurs at a single potential, rather than in two sequential steps separated by hundreds of millivolts, as is the case for previously reported MnBr(2, 2′‐bipyridine)(CO)3. Catalytic current enhancement is observed at voltages similar to MnBr(2, 2′‐bipyridine)(CO)3.